The Biography of Tilaar’s Thought in Historical Perception: Critical-TransformatIve Pedagogy - Gunawan, Indra; Setiawan, Johan (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to examine the intellectual biography of Henry Alexis Rudolf (HAR) Tilaar, one of Indonesia’s most prominent educational figures, particularly in the context of critical-transformative pedagogy. Tilaar viewed education not merely as a medium of knowledge transmission but as an instrument for liberating human beings from injustice, oppression, and social inequality by fostering critical awareness among individuals and society. The research employs the historical method with a literature review approach as the primary source to trace the dynamics of Tilaar’s educational thought over time. The findings reveal that Tilaar’s ideas evolved in an unusual trajectory: beginning with a conservative tendency in his youth, moving toward a constructive orientation during his service at Bappenas, and later becoming increasingly critical and radical after his retirement. This pattern stands in contrast to the general tendency among scholars, who often grow more conservative as their socio-economic status becomes more secure, whereas Tilaar became progressively more critical and radical in his educational perspectives.